Potensi Penerapan Integrated Farming System Pada Penyulingan Serai Wangi Dan Peternakan Ayam Petelur di Desa Wanakerta Kecamatan Cibatu - Nyimas Wangi; Salim; Ajeng Sabarini Muslimah (Cipasung Techno Pesantren: Jurnal Ilmiah, 2023)
The Sindang Wangi Farmer Group is one of the farmer groups in Wanakerta village that cultivates agriculture and animal husbandry in Kp. Babakan Kandang RT 04 RW 016. One of the farms and livestock in Wanakerta village is a citronella distillery and laying hens farm. The two businesses produce waste that can be recycled, namely hydrosol and organic fertilizer. This research was conducted to determine the potential of implementing an integrated farming system in citronella refining businesses and laying hens farms. By implementing the integrated farming system, the costs incurred by the citronella refining are Rp. 30,960,000 to Rp. 30,468,000. on laying hens farms costs Rp. 120,901,200 to Rp. 120,264,156. then for refining citronella it saves Rp. 492,000 while laying hens save Rp.637,044 per year.